Computing band structures of randomly-generated 2D photonic crystals with extreme learning machines - da Silva Ferreira, Adriano; Malheiros-Silveira, Gilliard Nardel [UNESP]; Hernández-Figueroa, Hugo Enrique (Optica Publishing Group, 2020)
We designed Extreme Learning Machines (ELM) for calculating band structures (BST) of randomly-generated bi-dimensional (2D) photonic crystals and demonstrated fast-training ELM models able to perform fast and accurate BST computations.